Price Ceilings as Focal Points for Tacit Collusion: Evidence from Credit Cards - Knittel, Christopher R; Stango, Victor (American Economic Review, 2003)
We test whether a nonbinding price ceiling may serve as a focal point for tacit collusion, using data from the credit card market during the 1980’s. Our empirical model can distinguish instances when firms match a binding ceiling from instances when firms tacitly collude at a nonbinding ceiling. The results suggest that tacit collusion at nonbinding state-level ceilings was prevalent during the early 1980’s, but that national integration of the market reduced the sustainability of tacit collusion by the end of the decade. The results highlight a perverse effect of price regulation.